Optimization of braided stent design for cerebral aneurysms: the role of wire cross-sectional geometry - Zhang, Aohua; Li, Xinru; Yang, Zhengbiao; Xie, Yutang; Wu, Tao; Xue, Yanru; Wang, Yanqin; Zhao, Yongwang; Chen, Weiyi; Sun, Chenming; Yin, Jinzhu; Zhang, Meng; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Flow-diverting stents are crucial for aneurysm treatment, with their structural design significantly impacting post-implantation hemodynamics. While clinically effective, opportunities remain to enhance their flexibility, flow diversion capability, and long-term safety through ongoing structural optimization. In this study, with Pipeline Embolization Device (PED) as a reference, four kinds of flow-diverting stents with different braided cross-section shapes (quadrilateral, hexagon, octagon, and decagon) were designed under the condition of keeping the amount of material constant. Firstly, pure bending loads are applied to each stent through finite element analysis, and its flexibility is evaluated by analyzing the torque-angle curve. Secondly, the computational fluid dynamics method was utilized to simulate the hemodynamic characteristics after the implantation of each stent. The results show that: (1) Under the condition of bending 60°, the decagonal stent has the best flexibility, followed by the quadrilateral one. (2) The overall blood flow distribution of stents with different cross-sections is similar, but there are differences in the local average flow velocity of the tumor cavity: the circular one is the highest, and the quadrilateral one is the lowest. (3) The wall pressure gradient change of the polygonal stent is gentler than that of the circular one. Among them, the wall pressure of the hexagonal and decagonal stents is the maximum and the average pressure in the cavity is the lowest. (4) The area of the low WSS region on the aneurysm wall is the largest in quadrilaterals and the smallest in circles. On the maternal artery segment, the hexagon is the largest and the quadrilateral is the smallest. Comprehensive comparison shows that quadrilateral and decagonal cross-section stents exhibit better comprehensive performance. Through the above research, theoretical support can be provided for the optimal design of flow-diverting stents structures.